MODELING OF PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT OF FUTURE SPECIALISTS PROFESSIONAL DEVELOPMENT - Sergeeva; Yankovskaya; Ladogina; Kemkhashvili; Bondarenko; Slepenok (Revista Inclusiones, 2019)
The article is devoted to the problem of psychological and pedagogical support of social workers professional development. The main content components of the structure of professional and personal development cover cognitive, motivational and value, social and perceptive, emotional and volitional and communicative spheres of human activity. The development of professional competence of the future specialist in social work is a process of relentless internal struggle for spiritual improvement and realization of creative potential, achievement of integrity and aspiration to get out of the state “the thing in self” to ascend to the “better self”. A necessary prerequisite for the creation of conditions for professional development of a social work specialist is the ability to choose ways of professional self-realization in the zone of uncertainty and the necessary presence of a zone of certainty. The presence of these zones makes it possible to actualize the motivation to choose the ways of specialists’ professional development. Actualization of motivation is more effective in the interaction of subjects, united by a common goal and common activities, which develop various forms of cooperation, the creative nature of the individual manifests.